The Impact of Globalization on Economic Growth in ASEAN - Suci, Stannia Cahaya; Asmara, Alla; Mulatsih, Sri (UI Scholars Hub, 2016)
The establishment of ASEAN (Association of Southeast Asian Nations) as one of the most highly-integrated regional organizations is the reflection of the process of globalization. This high integration is characterized by international cooperation in economic, social and political policies. One of the positive impacts of globalization itself is the increasing economic growth. However, this economic growth is disproportionately distributed among countries. In Southeast Asia, this is shown by the fact that the rising globalization in ASEAN is not always followed by the increase in economic growth. By using the KOF Index of Globalization that covers three main dimensions: economic integration, social integration, and political integration, this research paper looked into the impact of globalization on economic growth. Based on the panel data of six developing countries in ASEAN from 2006 to 2012, this research paper found that the overall index of globalization had positively and significantly impacted the economic growth in the region. Economic and political globalization also positively impacted the economic growth. However, the social globalization did not affect the growth. Inflation, infrastructure, quality of education, technological preparedness and government spending also had positive impact on economic growth.